PERBANDINGAN NYERI YANG TERJADI 24 JAM PASCA OPERASI PADA PENDERITA YANG DIBERIKAN ANESTESIA UMUM DAN ANESTESIA SPINAL - Muhammad, Fiska M.; Kumaat, Lucky; Posangi, Iddo (Universitas Sam Ratulangi, 2015)
Abstract: Pain can be described as an unpleasant sensory and emotional experience associated with tissue damage which has already occured or potentially will be occurred. General anesthesia is oftenly perfomed on a wide range of surgical procedures. There are two techniques of general anesthesia: inhalation anesthesia and intravenous anesthesia. Spinal anesthesia is one of the simplest and most reliable of regional anesthesia technique. This study aimed to compare the pain between general anesthesia and spinal anesthesia 24 hours post operative. This was an analytical prospective study. Samples were 24 patients consisting of 12 patients with general anesthesia and 12 patients with spinal anesthesia. The inclusion criteria were patients aged 20-60 years old, duration of operation 1-4 hours, and the operations were caesarean section and hysterectomy. The pain assessment used VAS score as well as blood pressure, pulse, and respiration. Data were statistically analyzed by using the Mann-Whitney test and showed a p-value 0.876. Conclusion: There was no significant difference in 24-hour-post-operative pain using VAS score among patients with general anesthesia and with spinal anesthesia.Keywords: VAS scores, general anesthesia, spinal anesthesia.Abstrak: Nyeri dapat digambarkan sebagai suatu pengalaman sensorik dan emosional yang tidak menyenangkan yang berkaitan dengan kerusakan jaringan yang sudah atau berpotensi terjadi. Anestesia umum sering dilalukan pada berbagai macam prosedur pembedahan dan terbagi atas anestesia inhalasi dan anestesia intravena. Anestesia spinal merupakan salah satu anestesia yang paling sederhana dan paling dapat diandalkan dari tehnik anestesia regional. Penelitian ini bertujuan untuk mengetahui perbandingan nyeri pada pemberian anestesia umum dan anestesia spinal 24 jam pasca operasi. Penelitian ini menggunakan metode analitik prospektif. Terdapat 24 sampel yang terbagi atas 12 penggunaan anestesia umum dan 12 penggunaan anestesia spinal, dengan kriteria rentang umur pasien 20-60 tahun, lama operasi 1-4 jam serta jenis pembedahan seksio sesarea dan histerektomi. Penilaian nyeri menggunakan skor VAS serta tekanan darah, nadi dan respirasi. Data diolah dengan menggunakan program SPSS versi 20. Hasil uji statistik Mann-Whitney mendapatkan nilai p= 0,876 yang menunjukkan tidak terdapat perbedaan bermakna dari skor VAS. 24 jam pasca operasi dengan anestesia umum dan anestesia spinal. Simpulan: Tidak terdapat perbedaan bermakna nyeri 24 jam pasca operaasi dinilai dengan skor VAS pada pemberian anestesia umum dan anestesia spinal.Kata kunci: Skor VAS, anestesia general, anestesia spinal